(untitled) (LEARNing Landscapes, 2019)
It is astonishing to observe, listen, and co-learn with children as they engage with music to expand beyond the possible with their meaning-making abilities—immersing themselves in a hundred languages of music inspired by Loris Malaguzzi. In the current study, I examine how children in a split Grade 1/2 class explore and represent the sounds associated with city landmarks through soundscape composition. In particular, I focus on how students partake in the negotiation of identity. As a result of that, I have come to discover that by listening to children’s soundscapes we may be able to feel something new about particular landmarks, contemplate its value to citizens, and learn more about the meaning making of children.